William Howard Taft : A Conservative's Conception of the Presidency - Anderson, Donald F., 1938- (Cornell University Press, 2019)
How a dedicated conservative perceived and used the powers of the presidency is here treated with authority, objectivity, and a dash of wit. The personal papers of William Howard Taft cast important new light on his aims and performance as chief executive. Making full use of the papers, Professor Anderson corrects previous studies of Taft that are either uncritical or unduly harsh, and offers instead a balanced and fair assessment.Taking a topical rather than a chronological approach to the Taft years, the author analyzes his accomplishments as party leader, administrator, legislator, leader of public opinion, and diplomat. The history of Taft's presidency, he concludes, illustrates many of the inherent strengths and weaknesses of a system of government that is reliant upon the will of the people for action and ultimate success.Comparing Taft with his eloquent and dynamic predecessor, Theodore Roosevelt, Anderson contrasts both their views of presidential power and their political styles. Finally, he places Taft in a larger historical context--as an apostle of constitutional democracy who valued the rule of law more than majority rule.